A collaborative immunohistochemical study of Drp1 and cortactin in the epithelial dysplasia and oral squamous cell carcinoma - Marina Nader; Samar Soliman; Shaimaa M. Yussif; Azza Abbas El-Sissi (Diagnostic Pathology)
Abstract Objectives Oral squamous cell carcinoma (OSCC) accounts for more than 90% of oral malignancies. The poorly understood molecular and cellular mechanisms underlying the pathogenesis of OSCC remain a subject of paramount importance. For epithelial dysplasia, invasion, and metastasis to occur, tumor cells require energy obtained from the mitochondria and phenotypic cellular changes in the actin cytoskeleton. Dynamin-related protein1 (Drp1) is one of the main mitochondrial proteins regulating the mitochondrial dynamics. Cortactin is an actin-binding protein that promotes the actin polymerization and rearrangement. The interplay between both proteins in OSCC remains elusive. The current study aimed to investigate the immunohistochemical (IHC) expression of Drp1 and cortactin in tissues revealing propagating OSCC cases. Methods The retrospective study was carried out on 35 formalin-fixed paraffin sections of nodal metastasizing OSCC cases selected from the Oncology Centre, Faculty of Medicine, Mansoura University archives from 2018 to 2023. Immunohistochemistry for Drp1 and cortactin was done. The immune reactivity of both proteins was evaluated using computer-assisted digital image analysis. Statistical analysis was performed to identify significant differences and correlations between both markers in tissues associated with progressing OSCC cases using Chi-Square, Monte Carlo, One-Way ANOVA, and Spearman tests. The p-value less than 0.05 was considered statistically significant. Results Drp1 expression was statistically significant to grades of primary OSCC (p = 0.015), while insignificant to grades of epithelial dysplasia (p = 0.123) and metastatic lymph nodes (LNs) (p = 0.212). Statistically significant differences between dysplastic epithelium & primary tumor, dysplastic epithelium & metastatic LNs, and primary tumor and metastatic LNs were observed (p values were 0.014, 0.001, 0.034, respectively). On the other hand, Cortactin expression revealed no statistically significant differences across the three groups. However, statistically significant differences between dysplastic epithelium & primary tumor, dysplastic epithelium & metastatic LNs, and primary tumor and metastatic LNs were found (p values were 0.014, 0.001, 0.034, respectively). Moreover, the Spearman test presented a strong positive correlation between Drp1 and cortactin expression in the studied cases. Conclusion Expressions of both Drp1 and cortactin relatively explain their great role in the propagation and the carcinogenesis of OSCC.